Nuclear Magnetic Resonance Under Extreme Conditions - (:unkn) unknown (My University, 2020)
Nuclear Magnetic Resonance (NMR) is a prime characterization tool used to understand the structures and interactions in organic molecules, crystals, as well as non-crystalline materials. However, until now, the combination of NMR with high-pressure instrumentation such as Diamond Anvil Cells (DAC) was deemed unfeasible due to the high spatial and electrical costs of standard NMR electromagnets or the regular refill of cryogenic liquids for superconducting magnets. Standard NMR techniques also raises technical difficulties when combining high-pressure instrumentation with high-temperature techniques such as laser heating. In the first part of this thesis, we present the development of a low-cost and space-saving table-top NMR system based on Halbach magnet arrays. We also demonstrate the use of this setup with a double-sided laser heating system for simultaneous in situ high-pressure and high-temperature studies. The feasibility of this setup is demonstrated by collecting 1H-NMR spectra of water at 25 GPa and 1063 (50) K. This introduced setup is shown to yield 1H-NMR signals of similar spectral resolution in DAC-based experiments as standard electromagnets operating around the same magnetic fields. In the second part of this thesis, we report low-temperature NMR measurements, that, along with other measurement techniques, reveal Charge Density Wave (CDW) order in the topological insulator Bi2Se3.
Keywords: Nuclear Magnetic Resonance